The Influence of Financial Performance And Corporate Governance On Green Banking Disclosure In Sharia Commercial Banks - Putri, Orsita Asmu; Putri, Rizky Nur Ayuningtyas (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
Islamic commercial banks do not fully disclose their green banking practices in sustainability reports, with an average disclosure covering only 40% of environmentally friendly activities. This study aims to analyze the impact of financial performance and corporate governance on green banking disclosure in Islamic commercial banks in Indonesia from 2020 to 2023. Data were obtained from annual reports, GCG reports, and sustainability reports of seven banks selected using a purposive sampling approach. Statistical data analysis was conducted using Eviews 10. The results indicate that green banking disclosure is significantly influenced by ROA, CAR, the board of directors, and the Sharia supervisory board simultaneously. Partially, ROA has a negative effect, CAR and the board of directors have a positive effect, while the Sharia supervisory board has no effect on green banking disclosure.